Advanced methods in molecular biology and biotechnology : a practical lab manual - Masoodi, Khalid Z; Lone, Sameena Maqbool; Rasool, Ravidha Saba (London : Academic Press, 2021)
Advanced Methods in Molecular Biology and Biotechnology: A Practical Lab Manual is a concise reference on common protocols and techniques for advanced molecular biology and biotechnology experimentation. Each chapter focuses on a different method, providing an overview before delving deeper into the procedure in a step-by-step approach. Techniques covered include genomic DNA extraction using cetyl trimethylammonium bromide (CTAB) and chloroform extraction, chromatographic techniques, ELISA, hybridization, gel electrophoresis, dot blot analysis and methods for studying polymerase chain reactions. Laboratory protocols and standard operating procedures for key equipment are also discussed, providing an instructive overview for lab work. This practical guide focuses on the latest advances and innovations in methods for molecular biology and biotechnology investigation, helping researchers and practitioners enhance and advance their own methodologies and take their work to the next level
BIBINDX
Keywords: Molecular biology -- Laboratory manuals; Biotechnology -- Laboratory manuals; Electronic books; Laboratory Manual; Laboratory manuals; Laboratory manuals; Manuels de laboratoire